2005
DOI: 10.1055/s-2005-873137
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Effect of Constituents fromHintonia standleyanain Streptozotocin-Induced Diabetic Rats

Abstract: An extract (100 mg/kg) of the stem bark of Hintonia standleyana caused a significant decrease in blood glucose levels in both normal and streptozotocin (STZ)-diabetic rats when compared with vehicle-treated groups (p < 0.05). From the active extract, 3- O- beta- D-glucopyranosyl-23,24-dihydrocucurbitacin F ( 1), 5- O-beta- D-glucopyranosyl-7-methoxy-3',4'-dihydroxy-4-phenylcoumarin ( 2) and 5- O-[ beta- D-apiofuranosyl-(1-->6)- beta- D-glucopyranosyl]-7-methoxy-3',4'-dihydroxy-4-phenylcoumarin ( 3) were isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…The administration of both Micromelum minutum seeds extract and Microminutinin coumarin Micromelum minutum seeds extract and Microminutinin coumarin to diabetic rats decrease body weight. These results are in agreement with that of Pari and Rajarajeswari [42] and Guerrero-Analco et al [35] who reported that the administration of coumarin to diabetic rats resulted in alterations in the metabolism of glucose with subsequent reduction in plasma glucose levels and body weight.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The administration of both Micromelum minutum seeds extract and Microminutinin coumarin Micromelum minutum seeds extract and Microminutinin coumarin to diabetic rats decrease body weight. These results are in agreement with that of Pari and Rajarajeswari [42] and Guerrero-Analco et al [35] who reported that the administration of coumarin to diabetic rats resulted in alterations in the metabolism of glucose with subsequent reduction in plasma glucose levels and body weight.…”
Section: Discussionsupporting
confidence: 83%
“…Coumarins also inhibited lipid peroxidation and increased the activity of antioxidants, superoxide dismutase and catalase [34]. Micromelum minutum seeds extract significantly reduced the blood glucose levels of diabetic rats indicating that the mechanism of action may be due to coumarin ingredient; where coumarin inhibits hyperglycemia [34,35]. Hyperglycemia inhibits antioxidants and its cellular transport.…”
Section: Discussionmentioning
confidence: 99%
“…1) were isolated from the stem-bark of H. standleyana and H. latiflora, respectively, as previously described (Guerrero-Analco, et al, 2005. Their purity was verified by HPLC and RMN.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Recently, we have studied the antidiabetic potential of H. standleyana and demonstrated that the extracts (50 mg/kg) or active compounds (15 mg/kg each time), twice a day during 30 days, provoked a significantly antihyperglycemic effect in streptozotocin-diabetic rats, restoring blood glucose levels near to or to normal values (Guerrero-Analco et al, 2005. Furthermore, this work demonstrated that the active principles of the Mexican copalchis were not only 4-phenylcoumarin glycosides but also cucurbitacins (Guerrero-Analco et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation